Comparative study on the synthesis and activity of metal oxides catalysts for production of FAME via transesterification of oils / Nur Umaira Ishak, Dr. Wan Zuraida Wan Kamis and Nur Alwani Ali Bashah - Ishak, Nur Umaira; Wan Kamis, Wan Zuraida; Ali Bashah, Nur Alwani (2020)
This paper reviews on the synthesis and activity of metal oxides catalyst for production of fatty acid methyl ester (FAME) via transesterification of oils. Transesterification process requires the presence of catalysts to react vegetables oils with methanol. Heterogeneous catalysts become the most prefer catalysts to be used due to the least problems to the overall reaction. Heterogeneous catalysts also can promote the best conditions to the operating systems compare to homogeneous catalyst and enzymes. However, catalytic activity of heterogeneous catalysts such as mixed metal oxides, sulphated metal oxides and sulphated zirconia can be influence by its reaction conditions. Paper gives a brief introduction on transesterification process and detailed review on the heterogeneous catalysts. It found that reaction conditions such as catalyst loading, reaction time, reaction temperature and methanol to oil molar ratio can give significant impact on the catalytic activity of the catalysts and thus, influence production of FAME. In addition, the effect of catalyst synthesis conditions such as calcination time, calcination temperature and metal ratio can give impact towards the catalytic activity and the FAME content. The work of many researchers on the effect reaction conditions and catalyst synthesis conditions based on various catalysts are reviewed, compared, and discussed.